Adalimumab-induced subacute lupus-like syndrome. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
Inhibitors of tumor necrosis factor (TNF) frequently induce the formation of antinuclear antibodies and anti-native DNA; however, they can also induce clinically evident lupus-like reactions in 0.2% of cases (4). You can talk about drug-induced lupus-like reaction when the following criteria are satisfied: presence of one or more symptoms of discoid, subacute or systemic lupus erythematosus, absence of previous history of lupus, taking a drug that is known to be responsible for lupus-like reactions and disappearance of the lesions with drug discontinuation. Among anti-TNF agents infliximab causes most frequently these reactions, while etanercept is less frequently responsible for these reacions; females are affected 10 times more frequently than males, and the average age is 44.9 years (3). The anti-TNF-induced lupus-like reaction is typically characterized by joint and skin lesions and occurs on average after 11 months after initiation of therapy (3). The cutaneous manifestations consist of a macular and papular rash, sometimes annular as in our case, erythema in sun-exposed sites, alopecia. There may be general symptoms such as fever, arthralgia, fatigue or myositis symptoms with elevation of muscle enzymes (1). The symptoms do not regress immediately after the anti-TFN suspension, but improve significantly in a period ranging from three weeks to six months. At least four pathogenetic hypotheses were advanced (2) about the mechanisms of the anti-TNF-induced lupus-like reaction; the long period of time required for the regression of the reaction after discontinuation of the drug underlines the importance of genetic predisposition: the drug would probably act only as a trigger in a subject genetically predisposed. (...).